Analysis Of Storability And The Level Preference Of Randang Using Different Types Of Chili - Wulandari, Celshea Tiara; Elida, Elida; Fridayati, Lucy; Mustika, Sari (Universitas Negeri Padang, 2023)
This study aims to analyze the shelf life and level of preference for beef rendang using curly red chilies and round red chilies. This research was carried out because no one had researched the storability of randang using curly red chilies and round red chilies along with the preference level of beef ribs using curly red chilies and round red chilies.is type of research is a mixed method (Mixed Method), this method is a combination of quantitative and qualitative descriptive methods. The study population was 3 expert panelists and 30 trained panelists. Data collection techniques used in this study were observation and questionnaires. The data analysis technique in this study used the t test. The storability of beef randang uses qualitative research methods. Based on the results of observations of storability analysis, on the 1st day the beef and bran randang were in good condition in terms of shape, aroma, taste, texture and color using curly chilies and round red chilies. On the 3rd day, beef and bran randang did not change in the two types of chili used. On the 6th day there was a change in shape, aroma, texture, color and taste which could not be tasted due to overgrown mushrooms which were found in the two types of chili used. As for the level of preference using quantitative research methods. The results of the hypothesis test showed that at a significant level of α = 0.05, it was obtained for the expert panelists that there was no significant difference between the use of curly red chilies and round red chilies. The results of the hypothesis test showed that at a significant level of α = 0.05, it was obtained for the expert panelists that there was a significant difference between the use of curly red chilies and round red chilies